Catalytic improvement and structural analysis of atrazine chlorohydrolase by site-saturation mutagenesis. Issue 7 (2nd July 2016) - Guo, Yuan; Zhao, Panjie; Zhang, Wenhao; Li, Xiaolong; Chen, Xiwen; Chen, Defu
Abstract: To improve the catalytic activity of atrazine chlorohydrolase (AtzA), amino acid residues involved in substrate binding (Gln71) and catalytic efficiency (Val12, Ile393, and Leu395) were targeted to generate site-saturation mutagenesis libraries. Seventeen variants were obtained through Haematococcus pluvialis -based screening, and their specific activities were 1.2–5.2-fold higher than that of the wild type. For these variants, Gln71 tended to be substituted by hydrophobic amino acids, Ile393 and Leu395 by polar ones, especially arginine, and Val12 by alanine, respectively. Q71R and Q71M significantly decreased the K m by enlarging the substrate-entry channel and affecting N -ethyl binding. Mutations at sites 393 and 395 significantly increased the k cat / K m, probably by improving the stability of the dual β-sheet domain and the whole enzyme, owing to hydrogen bond formation. In addition, the contradictory relationship between the substrate affinity improvement by Gln71 mutation and the catalytic efficiency improvement by the dual β-sheet domain modification was discussed. Graphical abstract: : Structrual modification in AtzA variants.